Metabolic factors related to the development of allergy A metabolomic analysis on metabolic proﬁles of children and their parents, venous and arterial umbilical cord blood and allergy development - Hartvigsson, Olle (My University, 2018)
Allergy is an increasing problem in the western world aﬀecting up to 25% of the population, leading to a decreased quality of life for the individuals and increased medical costs for society. Allergy is a complex disease and all the factors involved in the development of the disease are not yet established. The aim of this project was to identify diﬀerences in metabolic patterns in maternal and umbilical cord blood in relation to allergy development at one year of age. A second aim was to analyse diﬀerences in the metabolome between mothers, fathers and their newborn children and to investigate diﬀerences in metabolites in the childrens’ arterial and venous umbilical cord blood. The project was performed on data from 52 families participating in the NICE-cohort using multi- and univariate statistical tools. Usingmultivariatemodellingitwasnotpossibletodetectglobaldiﬀerencesbetween allergic and non-allergic children, possibly due to only seven out of the 52 children included developing allergy by the age of one year. Univariate models which examined each metabolite separately found several metabolites, mainly amino acids and monosaccharides, diﬀered signiﬁcantly between allergic and non-allergic children. Whencomparingsamplesfrommothers,fathersandchildrenitwasfoundthatmothers generally had higher amounts of α-tocopherol and fatty acids (mainly oleic-, linoleic- and linolenic acid) compared to paternal and infant samples, while infant samples contained high amounts of amino acids (mainly, glycylvaline, lysine, phenyalanine and tryptophan). The comparison between metabolic pattern in arterial and venous cord blood found that arterial blood contained more mono- and disaccharides (mainly deoxy galactose, glucose, sorbose and galactose) while venous blood contained more organic acids (including α-ketoglutaric acid and glutamic acid). Due to the low number of allergic children in this ongoing, no conclusions could be drawn about a speciﬁc metabolic pattern in relation to allergy. Hence, larger studies are needed to investigate the metabolic relationship to allergy development. Diﬀerencesbetweenmothersandnewbornsreﬂectsdiﬀerencesintheircatabolic/anabolicstates. Arterialandvenousdiﬀerencesmayindicatewhatsubstratesarebeing preferentially used by the newborn baby.
Keywords: Hälsovetenskaper; Livsmedelsvetenskap; Health Sciences; Food Science